Wellbeing and mental health amongst medical students in Canada. (17th November 2019) - Wilkes, Chris; Lewis, Thomas; Brager, Nancy; Bulloch, Andrew; MacMaster, Frank; Paget, Mike; Holm, Johanna; Farrell, Sarah Marie; Ventriglio, Antonio
Abstract: Across the world there is significant evidence that medical students have high levels of mental ill-health and psychological distress with subsequent concerning effects on personal and occupational functioning. In Canada, recent studies have demonstrated worrying levels of burnout and depressive symptoms among practising doctors. In common with other countries, Canadian medical students are also subject to a high-pressure environment – with long clinical weeks and significant stressors – and these soon-to-be doctors have been previously shown to already demonstrate high levels of burnout. We surveyed 69 medical students at the Cumming School of Medicine, Calgary regarding their wellbeing and mental health. 26% of the students had been diagnosed with a mental health condition prior to medical school, while 36% reported currently seeing a professional regarding their mental ill-health, with anxiety disorders forming the most commonly reported conditions. 83% reported their studies as a significant source of stress. 22% tested as CAGE positive and a number of students reported using other substances. 70% of medical students met specified case criteria for exhaustion on the Oldenburg Burnout Inventory. These findings speak to the need for access to mental health services, evidence-based individual counselling, and inclusive activities that fit within organisational frameworks to better improve the mental health and wellbeing of medical students in Canada.